A survey of pediatric CT doses in the Shanghai metropolitan area. (5th February 2019) - Lu, Heqing; Wang, Wengang; Li, Bin; Sun, Si; Zhang, Haowei
Abstract: The purpose of this study was to evaluate computed tomography (CT) doses in child examinees at different ages throughout the Shanghai metropolitan area. The head and body CT dose indices (CTDIs) of 50 CT scanners were tested by phantom measurements using standard imaging protocols. The values of CTDIw, CTDIvol and dose length product (DLP) were calculated and saved in a table along with the parameters of routine head and chest scans for different age groups of children and adults. The effective doses were estimated from the K-factors by age and DLP. The CTDIvol, DLP and effective dose for multi-detector row CT (MDCT) in children during routine head scans were larger than those for single-detector row CT (SDCT) and dual-detector row CT (DDCT). The CTDIvol, DLP and effective dose for MDCT and DDCT in children during routine chest scans were lower than those for SDCT. Radiation risks are higher for children in CT examinations compared to adults.